EFFECT OF WORK ASSESSMENT, WORK DISCIPLINE AND ORGANIZATIONAL COMMITMENT TO EMPLOYEE CAREER DEVELOPMENTPUBLIC WORKS AND SPATIAL ARRANGEMENTS REGENCY OF KARIMUN - Andykhatria, Andykhatria; Indrayani, Indrayani; Almansa Fitra, Mohamad; Syahril, Syahril; Hutasoit, Hasudungan; Wayan Catra Yasa, I (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
Competency-based HR management is a must, as a paradigm of the approach that is Career development is the process of improving skills, positions, and responsibilities. This study aims to determine the influence of performance assessment, work discipline and organizational commitment to employee career development. The population of this study is Civil Servants in the Public Works and Spatial Planning Office of Karimun Regency which amounts to 66 employees with a sample of 65 employees. The type of research used in this study is associative research. The method that can be used in this study is to use structural equation modeling (SEM) analysis based on variance, namely Partial Least Square (PLS). The research data was collected by questionnaire instrument. The results of the analysis in this study found that performance assessment had a positive and insignificant effect on employee career development (β = 0.270, p = 0.131) so it can be concluded that the results of the study rejected the first hypothesis. The results of the work discipline analysis showed a significant negative result with a probability value (β = -0.300, p = 0.026) so it can be concluded that the results of the study support the second hypothesis. The results of the organizational commitment analysis showed a significant positive result with a probability value (β = 0.293, p = 0.039) so that it can be concluded that the results of the study support the third hypothesis. The study also showed that 21% of employee career development variables were influenced by performance assessment variables, work disciplines and organizational commitments while another 79% were influenced by other variables.